Arsenate toxicity and metabolism in the halotolerant microalga Dunaliella salina under various phosphate regimes. Issue 6 (31st May 2016) - Wang, Ya; Zheng, Yanheng; Liu, Cong; Xu, Pingping; Li, Hao; Lin, Qiaoyun; Zhang, Chunhua; Ge, Ying
Abstract : Phosphate (PO4 3− ) mediates As(v ) uptake and transformation in Dunaliella salina, thereby affecting As removal ability of this exceptionally halotolerant microalga. Abstract : Microalgae play an important role in arsenic (As) biogeochemical cycles as they are capable of accumulating and metabolizing this metalloid efficiently. This study aimed to investigate the toxicity, accumulation and transformation of arsenate (As(v )) in Dunaliella salina, an exceptionally halotolerant microalga, under various phosphate (PO4 3− ) regimes. The results of the 72-h toxicity test showed that D. salina was tolerant to As(v ). In addition, the toxicity of As(v ) was mitigated by an increased PO4 3− supply. D. salina resisted the adverse effects of As(v ) through the suppression of As uptake, enhancement of As reduction, methylation in the cell and excretion from the cell. Our study revealed that D. salina reduced As(v ) toxicity using different strategies, i.e., reduction of As uptake upon acute As stress (24 h) and increase of As efflux following chronic As exposure (9 day). Moreover, PO4 3− strongly affected the adsorption, uptake and transformation of As(v ) in D. salina . As(v ) reduction, DMA production and As excretion were enhanced under P-limited conditions (0.112 mg L −1 ) or upon higher As(v ) exposure (1120 μg L −1 ). Furthermore, PO4 3− had a significant influence on the As removal ability of D. salina . A high As removal efficiency (>95.6%) was observed in the 5-day cultures at an initial As concentration of 11.2 μg L −1 and PO4 3− of 0.112 and 1.12 mg L −1 . However, only 10.9% of total As was removed under 11.2 mg L −1 PO4 3− after 9 days of incubation. The findings of this study illustrate the pivotal roles of extracellular PO4 3− in As(v ) toxicity and metabolism, and the results may be relevant for future research on the minimization of As contamination in algal products as well as on the enhancement of As removal from the environment.